(untitled) (Global Journals of Research in Engineering, 2022)
This article aims to solve the problems of supervision and PI controller of an industrial thermal system (the industrial static refrigerator). The structure of an industrial system from the point of view of the external model operates in several modes of operation (normal and abnormal). For this external model, we have two problems, the first problem is a fault location problem because we are talking about a global operation of the system and the second problem is a problem of visualization of the phenomenon of switching between the operating modes of the system. For this, in this article we have integrated two other models to solve the problems in question. For the localization problem, we used the bond graph model. This model, by its graphic nature and the use of a unified language, allows to model the industrial system element by element from which it helps the user not only to detect defects, but also to locate them when they appear in the system. For the visualization problem, we used the transfer function model. This model defines the relationship between the input and an output variable, this relationship allows us to visualize the appearance of the output signals for each mode. These techniques have been applied to monitor an industrial refrigerator, and analyzes and simulations are determined to validate the reliability of these models.